Redistributive impacts of civil war: The case of Côte d'Ivoire - Vladimír Hlásny (Luxembourg Income Study (LIS), 2023)
Many of the world's LDCs are plagued by recurring conflict. Conflict impedes sustainable development through various channels, creating conditions conducive to further conflict. Conflict has redistributive impacts, particularly when it erupts in resource-rich countries. Between 2002 and 2011, Côte d'Ivoire faced off two spells of civil war (2002-2007 and 2010-2011) along geographic, religious, ethno-linguistic and economic lines. Poverty and inequality rose throughout the decade. We investigate how the civil war and the associated changes in the political balance impinged on the economic performance of the affected geographic/ religious/ ethnic groups at various income deciles. Growth incidence curves before-after conflict illustrate the income changes experienced by the respective socioeconomic groups. Accounting for distortions due to individual selection and general-equilibrium spillovers, unconditional quantile regressions fitted by the means of a recentered influence function are used to isolate between-group gaps in household incomes attributable to conflict. The results on microdata from three Household Living Standards Surveys (2002, 2008 and 2015) confirm that as the political tide shifted, the economic fortunes of the affected groups turned. Previously marginalized communities - the northern, Gour and Mandé ethnic, and non-Christian groups - have bridged some of their disadvantage in terms of their endowments and the market returns on them. These changes are clearest in the upper half of the income spectrum, leading to profound changes in social order.
Keywords: D74; D31; D63; N37; O55; 330; Conflict and inequality; civil war; income gap decomposition; growth incidence curve; recentered influence function; unconditional quantile regression; Côte d'Ivoire; Luxembourg Income Study; Income distribution; redistribution; ethnicity; politics